Pengaruh Insentif Pajak, Account Representative Terhadap Kepatuhan Wajib Pajak Dengan Self Assessment System Sebagai Pemoderasi - Sari, Novita (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2022)
This study was conducted to test whether tax incentives and account representatives have a strong enough influence to increase individual taxpayer compliance during covid-19. Meanwhile, this study was also undertaken to determine whether tax incentives and account representatives can influence individual taxpayers to obey in calculating, depositing, and reporting annual notification letters in a timely manner. This study uses primary data obtained by distributing questionnaires to individual taxpayers in Malang. The data is quantitative, which will later be analyzed using the SPSS 25 application. This study found that tax incentives and account representatives have a positive and significant effect on individual taxpayer compliance. This study found that tax incentives had an insignificant impact on taxpayer compliance, and account representatives substantially affected individual taxpayer compliance. While the self-assessment system variable has not been able to moderate tax incentive policies on taxpayer compliance but can moderate the performance of account representatives on taxpayer compliance.